THE CHARACTERIZATION OF THE MAIN CHARACTER IN GONE GIRL FILM - Cindy Putri and Meisuri (LINGUISTICA, 2017)
This article deals with the characterization of the main character in Gone Girl film. The study was aimed to find out the characterizations and the most dominant characteristic of Amy Elliot Dunne in the film. The study was conducted by applying descriptive qualitative method. The data of the study were taken from all utterances of Amy’s dialogues and monologues which were transcribed into 39 selected sentences. The findings of the study were: (1) the kinds of Amy characterizations: intelligent (17.94%), perfectionist (12.82%), insecure (28.20%), liar (33.33%) and vengeful (7.69%); (2) the most dominant characteristic of Amy was liar (33.33%).